2022
DOI: 10.3390/nu14071340
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Faecal Microbiota and Small ncRNAs in Autism: Detection of miRNAs and piRNAs with Possible Implications in Host–Gut Microbiota Cross-Talk

Abstract: Intestinal microorganisms impact health by maintaining gut homeostasis and shaping the host immunity, while gut dysbiosis associates with many conditions, including autism, a complex neurodevelopmental disorder with multifactorial aetiology. In autism, gut dysbiosis correlates with symptom severity and is characterised by a reduced bacterial variability and a diminished beneficial commensal relationship. Microbiota can influence the expression of host microRNAs that, in turn, regulate the growth of intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 132 publications
(157 reference statements)
2
22
0
Order By: Relevance
“…Six studies revealed a decreased Bacteroidetes/Firmicutes ratio in ASD [ 30 , 34 , 41 , 49 , 54 , 62 ]. Contradictory findings were reported by the same number of authors [ 36 , 38 , 40 , 52 , 53 , 57 ], and in four other studies, no significant differences were observed [ 28 , 37 , 39 , 64 ]. A similar number of studies reported decreased, increased, or no specific difference in the abundance of Bacteroidetes , Firmicutes , and Actinobacteria .…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Six studies revealed a decreased Bacteroidetes/Firmicutes ratio in ASD [ 30 , 34 , 41 , 49 , 54 , 62 ]. Contradictory findings were reported by the same number of authors [ 36 , 38 , 40 , 52 , 53 , 57 ], and in four other studies, no significant differences were observed [ 28 , 37 , 39 , 64 ]. A similar number of studies reported decreased, increased, or no specific difference in the abundance of Bacteroidetes , Firmicutes , and Actinobacteria .…”
Section: Resultssupporting
confidence: 52%
“…Lower amounts of Prevotella or certain Prevotella species in ASD patients were found in several studies [ 25 , 30 , 31 , 37 ]. In contrast, some authors found the opposite [ 33 , 40 , 42 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using fluid samples such as blood and cerebrospinal fluid or brain-associated tissues, such as the cortex and basolateral amygdala, the associations between miRNAs and depression in humans have been reported in a review article 24 , despite lacking robust findings to serve as potential biomarkers for depression. Recently, an autism-associated study using fecal samples found that autistic patients with gut dysbiosis were also associated with transcriptional modulators, which were involved in intestinal permeability and inflammation 6 . However, as far as we know, there are no studies exploring miRNAs' roles in fecal samples for depression.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, depressed individuals commonly reported gastrointestinal dysfunction and disordered bowel habit 3 , indicating the link between the gut and brain health. In this regard, recent work exploring the causal effects of gut microbiota on human health has suggested the interactions between gut microbiota and host microRNAs (miRNAs) [4][5][6] .…”
mentioning
confidence: 99%